PECULIARITIES OF CONNECTIONS RHEOVASOGRAPHY INDICES AND INDICATORS TONE OF HIP ARTERY WITH ANTHROPOMETRIC AND SOMATOTYPOLOGICAL PARAMETERS OF HEALTHY URBAN BOYS AND GIRLS PODOLIA - Вадзюк, С.Н.; Гунас, І.В.; Цвинтарний, А.В. (World of Medicine and Biology, 2014)
In 148 healthy boys aged from 17 to 21 years and 160 women aged from 16 to 20 years, in the third generation residents of the region Podolsky Ukraine set features links rheovasography indices and indicators of arterial tone hip with anthropometric, somatotypological parameters and component performance composition of body weight. Established following numerous statistically significant correlation: in girls - straight weak and medium strength speed performance rheovasography hip with most measures the thickness of skin-folds of fat on the trunk and the lower limbs and inverse weak force with weight and body surface area, nearly half circumferences distal parts of the limbs and muscle component of body weight; reverse weak force indicator tone arteries of small and medium caliber half -width parameters of distal epiphysis of bones of the extremities , most measures the thickness of the skin- fat folds on the trunk and the lower limbs, endomorph component of somatotype and bone and fat components of body weight; in boys - straight, mostly poor power performance arterial tone medium and small caliber of most measures the thickness of skin- folds of fat on the trunk and the lower limbs, endomorph component of somatotype and fat component of body weight; reverse mainly weak force, all speed performance reovazohraphy hip with circumference shoulder and chest, pectoral cross mid-size, mesomorphic somatotype component and muscle component of body weight.
Keywords: rheovasography; anthropometric parameters; correlations; healthy boys and girls